ANALISIS PENDAPATAN USAHA TANI JAGUNG DI KELURAHAN KAWANGKOAN BAWAH KABUPATEN MINAHASA SELATAN - Mononimbar, Dannis Nugraha Noel; Laoh, Olly Esry Harryani; Tambas, Jane Sulinda (Sam Ratulangi University, 2022)
This study aims to analyze the income of corn farming in Kawangkoan Bawah Village, South Minahasa Regency. This research was carried out from June 2021 to October 2021 starting from research preparation to the preparation of the research report. The data used in this study consisted of primary and secondary data. Primary data is data obtained directly from the field through interviews using questionnaires with respondents while secondary data is data obtained from government agencies such as government agencies at the research location, Central Bureau of Statistics, Ministry of Agriculture and other related parties. Sampling in this study were corn farmers from the village of Lower Kawangkoan who were selected using a simple random sampling technique. Respondents needed in this study were 30 (thirty) respondents. The results showed that the total cost of the production component of corn farming in kawangkoan bawah village was Rp. 5,103,379 per planting season. Net income on corn farming per ha in Kawangkoan Bawah Villaget Per one planting season is Rp. 21,246,430.